Fracture of the Fabella: A Rare Injury in Knee Trauma - André Rodrigues Façanha Barreto; Francisco Abaeté das Chagas-Neto; M.D. Crema; Mário Müller Lorenzato; Mariana Tiemi Teixeira Kobayashi; Carlos Monteiro; Marcello Henrique Nogueira‐Barbosa (2012)
We present a case of a 21-year-old woman sustaining a traumatic [fabellar] fracture following a motor vehicle accident. The fabellar fracture was confirmed on plain films, which prompted further evaluation of the knee with ultrasound and magnetic resonance imaging to evaluate other possible associated injuries. Fracture of the fabella is a rare condition. Clinically, patients present with posterolateral knee pain, edema, and limited knee extension. Occasionally these symptoms may be very subtle, delaying the correct diagnosis and patient management.